Tombstone courage - Jance, Judith A., 1944- (Joanna Brady Mysteries, 2009)
When drug dealers murdered her lawman husband, Joanna Brady vowed she would carry on his good work no matter what the cost. With grit, courage, and dogged determination, she challenged the status quo-and won. Now, as newly elected Sheriff of Cochise County, Arizona, she must battle the prejudice and hostility of a mistrustful, male-dominated police force and solve a grisly double homicide that threatens to tear the sleepy desert community to pieces. For the two bodies baking in the harsh Southwestern sun are connected by sinister threads that reach back generations-and by devastating family secrets of greed, hatred, and shocking abuse that could destroy the innocent along with the guilty.